A Review of Northern Ireland Seal Count Data 1992-2017 : Investigating population trends and recommendations for future monitoring.: Investigating population trends and recommendations for future monitoring. ([2018]) - Culloch, Ross M; Horne, Nicholas; Kregting, Louise; Centre for Environmental Data; Recording; Queen's University Belfast
No abstract available